2019
DOI: 10.1016/j.bbmt.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hematopoietic Stem Cell Transplantation on Dental Development

Abstract: To investigate dental development in patients treated with a hematopoietic stem cell transplantation (HSCT), 42 children and young adults who were under 12 years old at time of HSCT were examined for dental agenesis, microdontia, and root-to-crown ratio. Conditioning regimens were total body irradiation (TBI) based in 12 patients, busulfan based in 21 patients, and 9 patients had other chemotherapeutic agents. Sixteen patients were <3 years old, 9 patients were 3 to 6 years old, and 17 patients were 6 to 12 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…HSCT in younger children, especially those below 3 years old, is highly related to dental problems, including agenesis, microdontia, enamel hypoplasia, and extensive caries. Although the prevalence was relatively low in this study, we confirmed the results reported previously 12,13 …”
Section: Discussionsupporting
confidence: 92%
“…HSCT in younger children, especially those below 3 years old, is highly related to dental problems, including agenesis, microdontia, enamel hypoplasia, and extensive caries. Although the prevalence was relatively low in this study, we confirmed the results reported previously 12,13 …”
Section: Discussionsupporting
confidence: 92%
“…The early detection of craniofacial deformities is important to provide childhood HSCT survivors proper care and mitigate the quality of life impairment associated with oncologic treatments. Panoramic radiographs present as a trustworthy and cost-effective tool for craniofacial growth screening early malocclusion diagnosis ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their myelosuppressive action, cytostatics lead to thrombocytopenia and granulocytopenia. Thrombocytopenia results in onset of petechiae in oral mucosa and frequent bleeding in the oral cavity, and granulocytopenia leads to an increased risk of the occurrence of oral infections [36]. Due to changes in oral mucous membrane and parenchyma of the salivary glands after the application of therapy for hematologic malignancies, as well as stress, in the period prior to the tissue and cell transplantation, reduction in the secretion of stimulated saliva may be observed.…”
Section: Oral Changes Before Transplantation Of Hematopoietic Stem Cellmentioning
confidence: 99%
“…In children subjected to high doses of chemotherapy and radiation therapy during treatment of malignant diseases more frequent occurrence of developmental dental anomalies is observed several years after the hematopoietic stem cell transplantation. Structural irregularities in the teeth, mineralization disorders of hard dental tissues, irregularities in the length and shape of the teeth roots, reduced tooth crown size, as well as the lack of a smaller or greater number of teeth may occur [36,41].…”
Section: Oral Changes After Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%